Wilson's practical meat inspection - Wilson, William ([Ames, Iowa] [Blackwell Pub.], 2005)
"Awareness of food safety and its economic significance has never been higher after public alarm following the BSE crisis and the Foot-and-Mouth outbreak.

This classic text is an essential handbook for all persons involved in meat inspection and the meat industry seeking information on the latest diseases and parasites. Now in its seventh edition, it has been revised to reflect the latest knowledge of BSE, Foot-and-Mouth and TB. Information on specific diseases, parasites and physiological processes has been updated and the latest legislation included. As well as this, a new chapter on illegal meat imports has been added, with the aim of helping the detection of illegal meat and ensuring its removal from the food chain.
• Well-established and respected reference for all those seeking hands-on, practical information;
• Details the latest reports on diseases and includes crucial information on meat related legislation."
Includes bibliographical references (pages 295-296) and index (pages 297-306).
Keywords: Meat inspection